Topical issues concerning modern lipid-lowering therapy - Andrey V. Susekov (ZAO "Consilium Medicum", 2022)
Hypercholesterolemia (high levels of atherogenic lipoproteins) is the main modifiable cardiovascular risk factor in most of the populations, including the Russian population. 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors (statins) have been used in clinical practice for more than 40 years and have a substantial evidence-based proof of efficacy and safety. Unfortunately, the most of the patients with high cardiovascular risk, including the Russian Federation, still receive initial statin doses and only in 10% of the cases we can reach the recommended target level of low-density lipoprotein cholesterol. This article deals with the current principles of statin therapy according to the latest guidelines and shows updated information concerning the optimization of statin therapy in the elderly and in patients with chronic kidney disease. This article, as well, shows the safety of applying HMG-CoA reductase inhibitors (impact on muscles, liver and cognitive impairments). In addition, the review presents the algorithms for the combination therapy of statins and ezetimibe.